Biodegradable microcapsules based on composite materials and synthetic methods
Patent Information
- Application Number
- CN202180092690.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-12-14
- Filing Date
- 2021-01-11
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2041-01-11
AI Technical Summary
它们通常无法足够好地包封(挥发性)芯材料,导致机械特性以及在不同洗涤剂和织物柔软剂中的稳定性较差
[0117] The results show ( Figure 8The reference compound degraded well. Degradation was greater than 60% after only 5 days. This confirms the activity of the microorganisms, the suitability of the test, and the validity of the results. The sample also degraded well in the test. Greater than 80% (85±3%) degradation was achieved during the 40-day test. This degradation level was reached on day 17 of the test, followed by a 3-day lag period. Rapid degradation of the sample was also confirmed in the test using samples with added ATU (added to prevent nitrification and the resulting oxygen consumption), as complete degradation (99±2%) was achieved in this case. Since the degradation in the sample with ATU was comparable to or even higher than that in the sample without ATU, it can be concluded that the difference between the two curves is due to experimental error or more precisely, due to the test principle, and that no nitrification occurred. This means that the actual biodegradation of the sample reached as high as 85%, with very little non-biodegradation (6±0%). It can be concluded that the degradation level obtained is primarily a result of microbial activity (biodegradation).
Smart Images

Figure BDA0004371803560000111 
Figure BDA0004371803560000141 
Figure HDA0004371803570000011
Abstract
Description
[0001] This invention relates to biodegradable microcapsules having membrane walls formed of biodegradable composite materials and methods for synthesizing the same. The biodegradable microcapsules of this invention are in the form of encapsulated particles in an aqueous dispersion for encapsulating fragrances, active pharmaceutical ingredients, pesticides, and other materials, which are subsequently used in fabric softeners, detergents, pesticides, coatings, cosmetics, and similar products. Background Technology
[0002] Microencapsulation is a well-established method for encapsulating active ingredients with a membrane (also known as a wall). The primary purpose of microencapsulation is to protect the active ingredients within the core from external influences and to prolong or control the release of these active ingredients. The final product of microencapsulation is a microcapsule, which consists of a core material containing at least one active ingredient and a wall. Typically, the size of microcapsules is around 10... -6 m to 10 -4 Within the range of m.
[0003] Polyurea, polyacrylates, polyurethanes, and similar microcapsules are well-known and widely used in many fields, particularly in the pharmaceutical, fragrance, and personal care product industries. Methods and techniques for synthesizing microcapsules vary depending on the field. The type of technology chosen depends on the desired wall material, the properties of the core material, and the end application. Based on the formation of the wall material, microencapsulation techniques can generally be categorized into chemical and physical techniques. This document provides only a brief overview of the microencapsulation technique relevant to this invention, namely, the synthesis of microcapsules from emulsions.
[0004] A common method for preparing microcapsules from emulsions is interfacial polymerization. First, a surface-active agent is used to form a stable emulsion of two immiscible fluids by dispersing one phase in another. When using an aqueous and an oil phase, water-in-oil (W / O) or oil-in-water (O / W) emulsions can be prepared. In this invention, we will focus on O / W emulsions because this invention relates to the encapsulation of organic active compounds. Adding monomers to the individual phases that form the final capsule membrane is characteristic of interfacial polymerization. By adding one type of monomer to each phase, a reaction occurs between the monomers in the interfacial phases of the emulsion droplets. After the formation of a stable emulsion, a polymerization process (temperature, pH, catalyst, etc.) is initiated, resulting in the formation of the final polymer and the trapping of the individual droplets in the membrane.
[0005] The above technologies are commonly used to encapsulate fragrances because they allow for the slow release of the core material, thus allowing for a long-lasting aroma (US20150044262A1), while also protecting the fragrance from oxidation and rapid evaporation. In intensive agriculture, the same technologies allow for the sustained efficacy of pest control agents and insecticides, while also protecting them from UV degradation (EP2403333A1, US5160529A, US4956129A). In the described examples, polyurea and melamine-formaldehyde microcapsules are commonly used. In particular, the use of the latter is increasingly restricted because it contains trace amounts of toxic formaldehyde.
[0006] Other methods for microencapsulation from emulsions include suspension polymerization and coagulation. In suspension polymerization, the aqueous (continuous) phase does not contain monomers but rather a water-soluble initiator, which initiates polymerization at the interface. An example of suspension polymerization is the synthesis of polyacrylate microcapsules.
[0007] In coagulation, microcapsules form as colloidal systems with phase separation. One phase is rich in macromolecules (the coagulated layer), while the other phase is poor in macromolecules. The two phases exist in equilibrium. Phase separation is promoted by changes in parameters such as pH and / or temperature, or by the addition of a coagulant. This reduces the solvation shell, thereby inducing phase separation. The resulting coagulated layer then positions itself at the phase interface of the emulsion droplets, encapsulating them within the membrane. This membrane can then be further chemically crosslinked.
[0008] It is important to note that microcapsules obtained using different techniques possess different properties. Since most polymers are inert, chemical encapsulation techniques such as interfacial polymerization and suspension polymerization allow for the formation of more resistant microcapsules. Microcapsules obtained in these ways also enable the preparation of capsules with lower porosity because they can be more crosslinked to any desired degree. Such capsules are preferably used with volatile compounds such as fragrances and ether oils. In the case of physical encapsulation techniques and physicochemical encapsulation techniques such as coagulation, the membranes are less crosslinked and resistant because it is generally preferred to allow the wall material to degrade slowly and release the core material. These membranes are composed of natural polymers such as polysaccharides and / or proteins. These encapsulation techniques are preferred for use in the pharmaceutical and food industries, where the microcapsules must be biocompatible and / or biodegradable. The biodegradable microcapsules described in this invention are primarily synthesized from emulsions.
[0009] With increasing focus on sustainable development, the issue of non-degradable microplastics is rapidly gaining attention. Microplastics (including microcapsules) made from cross-linked polymers, found in cosmetics and personal care products, are particularly problematic because they are washed into the ocean. There, they slowly degrade for centuries, or, in the worst case, accumulate in wildlife.
[0010] While biodegradable microcapsules derived from natural materials do exist, they are not suitable for certain applications. They often fail to encapsulate (volatile) core materials well enough, resulting in poorer mechanical properties and stability in various detergents and fabric softeners.
[0011] This problem is solved by microcapsules derived from composite materials based on the present invention. Despite the low percentage of cross-linked material, these capsules exhibit good mechanical properties and are stable over long periods in alkaline detergents and fabric softeners. The OECD 301 closed-bottle biodegradability test in an enclosed respirometer measuring the uptake of oxygen has demonstrated that the microcapsules derived from composite materials based on the present invention are biodegradable. Summary of the Invention
[0012] This invention relates to a method for encapsulating liquid organic components or solutions that are immiscible with water. It also relates to the synthesis of biodegradable microcapsule slurries and the biodegradable microcapsules themselves. Microcapsules prepared according to this invention are particularly suitable for fabric softeners, detergents, personal care products, and pharmaceuticals. This invention is not limited to the above applications and is applicable to the encapsulation of any active compound that allows encapsulation using the methods described herein. The microencapsulation steps described in this invention allow for the encapsulation of a broad spectrum of liquid organic compounds (or solutions) into microcapsules made of biodegradable composite materials.
[0013] The invention is described in more detail below and is presented in the accompanying drawings as follows:
[0014] Figure 1 SEM images of cross-sections of biodegradable microcapsules obtained as described in this invention are shown.
[0015] Figure 2 A comparison of SEM images of biodegradable microcapsules (left) and classic polymer microcapsules (right) obtained as described in this invention is shown.
[0016] Figure 3 SEM images of the morphology of the biodegradable microcapsules obtained as described in this invention are shown.
[0017] Figure 4 SEM images of filler-filled pores in the membrane of the biodegradable microcapsules obtained as described in this invention are shown.
[0018] Figure 5SEM images of molten filler on the carrier polymer framework of biodegradable microcapsules obtained as described in this invention are shown.
[0019] Figure 6 The images show a filler-filled biodegradable microcapsule (left) and an unfiller-filled biodegradable microcapsule (right) obtained as described in this invention after 7 days in a fabric softener substrate.
[0020] Figure 7 The results of the rapid breath measurement biodegradability test are shown.
[0021] Figure 8 The results of biodegradability over time are shown.
[0022] The biodegradable microcapsules of the present invention are composed of the following:
[0023] - A core material, said core material comprising at least one water-immiscible liquid active component, and
[0024] - A membrane containing a core-encapsulating material, wherein the membrane comprises a composite material containing a carrier polymer framework and at least one filler embedded in the pores of the polymer framework and deposited on the surface of the carrier polymer framework, wherein the carrier polymer framework comprises at least one polymer, and the filler is a lipophilic biodegradable organic compound that is solid at room temperature and has a melting temperature above 40°C, wherein the thickness of the membrane is in the range of 20 nm to 200 nm, and the diameter of the microcapsules is in the range of 1 μm to 50 μm.
[0025] The core material portion of the final product (microcapsule slurry) as an aqueous dispersion is 20% to 40% (by weight), and in dry microcapsules it is 75% to 95%.
[0026] The filler portion is 5% to 95% (by weight) relative to the carrier polymer framework, preferably in the range of 50% to 90% (by weight).
[0027] Given that the synthesis of biodegradable microcapsules as described in this invention is carried out via interfacial polymerization in an emulsion, the active component to be encapsulated preferably has the following characteristics:
[0028] - It does not mix with water, and all compounds present in the core material have a logP (partition factor) value greater than 2;
[0029] - It allows the filler to be mixed with the active component at elevated temperatures, while remaining inert to the filler material (the active component should not react with the filler);
[0030] - It allows for the mixing of reactants required for polymerization while remaining inert to these reactants (the active component should not react with the reactants required for polymerization);
[0031] - Because the synthesis steps are carried out at elevated temperatures, it is stable at temperatures up to 100°C.
[0032] Suitable active ingredients are selected from fragrances, pigments, pesticides, pharmaceutical ingredients, phase change materials, ether oils (such as eucalyptus oil, lavender oil, rose oil, common valerian oil, basil oil, juniper oil, lemongrass oil, etc.), other oils (such as palm oil, coconut oil, castor oil, sunflower oil, olive oil, mineral oil) and photochromic materials.
[0033] The active ingredient in the microcapsule core can exist alone or dissolved in a suitable organic solvent. A suitable organic solvent is immiscible with water and has a log P value greater than 2. The organic solvent should be compatible with the active ingredient and the reactants used; this means that the organic solvent should not react with the active ingredient and the reactants used.
[0034] Suitable polymers are selected from polyurea, polyurethane, polyacrylate, polyamide, polyester, gelatin, or other polymers suitable for emulsion polymerization.
[0035] When selecting suitable fillers, their biodegradability and miscibility in various organic solvents are crucial. The filler's miscibility in solvents should allow it to be miscible at higher temperatures (above 40°C) but immiscible at room temperature, enabling maximum crystallization when cooled in a controlled manner to temperatures below 40°C. Suitable fillers are selected from waxes, paraffins, fatty acids, and polyethylene glycols, whose solubility is highly temperature-dependent. The most suitable fillers are highly crystalline waxes with crystallization temperatures above 40°C.
[0036] The synthesis of an aqueous dispersion of biodegradable microcapsules from an emulsion as described in this invention includes the following steps:
[0037] a) Preparation of an oil phase, wherein the core material to be encapsulated (active ingredient, and organic solvent (if used)) is mixed with filler and reactants suitable for forming a carrier polymer framework at a temperature of 40°C to 70°C, wherein the reactants are chemicals that are mixed with the core material and react during the polymerization stage to form a carrier polymer framework comprising at least one polymer.
[0038] b) Prepare an aqueous phase at a temperature above 40°C, said aqueous phase comprising an aqueous solution of a biodegradable surfactant;
[0039] c) A stable emulsion is prepared at a temperature of 40°C to 70°C, wherein the oil phase is emulsified in an aqueous phase to form dispersed or emulsified droplets of the same size as the microcapsules formed.
[0040] d) A carrier polymer framework forming a film from at least one polymer, wherein the addition of a water-soluble reactant to a stabilizing emulsion triggers the formation of the carrier polymer framework at the phase boundary around the dispersed droplets, and thus triggers the formation of an aqueous dispersion of microcapsules;
[0041] e) The aqueous dispersion of the microcapsules is controlled to a temperature of 10°C to 25°C, whereby the filler crystallizes and embeds itself in the pores and is deposited on the surface of the carrier polymer framework of the membrane, thereby forming a final aqueous dispersion of biodegradable microcapsules with a mass fraction of 25% to 50%.
[0042] Optionally, the synthesis of an aqueous dispersion of biodegradable microcapsules further includes step f), wherein a stabilizer is added to the aqueous dispersion of the microcapsules to prevent separation of the microcapsules from the aqueous phase in the aqueous dispersion, and / or additional reagents are added to ensure the end of polymerization and to eliminate excess reactants, and / or a pH adjuster is added to set the pH of the aqueous dispersion to a desired value, primarily to better ensure the stability of the aqueous dispersion or to make the aqueous dispersion in the final product easier to use.
[0043] Step f) can be after step d), meaning the additive is added to the aqueous dispersion before controlled cooling, or step f) can be after step e).
[0044] The selection of fillers with different melting temperatures directly affects their crystallization during controlled cooling. When the aqueous dispersion is cooled below the melt temperature of the filler, the filler has a strong tendency to form crystals (exhibiting self-nucleation properties), leading to eventual separation of the filler from the carrier oil phase. This property of the filler was used in the synthesis of biodegradable microcapsules. After the polymerization step is completed and the polymer carrier framework is thus formed, the aqueous dispersion of the biodegradable microcapsules is slowly cooled to a temperature of 10°C to 25°C, causing the filler to separate from the core material and crystallize on the surface of the carrier framework, filling its pores and thus increasing the membrane stiffness and reducing its permeability. The resulting product is a stable dispersion of 25% to 50% of the microcapsules by mass.
[0045] The choice of reactants added to the oil phase and water-soluble reactants added to the aqueous phase depends on the choice of polymers that form the support polymer framework.
[0046] For the formation of a carrier polymer framework from polyurea and polyurethane, suitable reactants are selected from isocyanates, particularly aromatic and aliphatic isocyanates having at least two functional groups. Reactants are primarily selected from aromatic and aliphatic isocyanates, and include toluene diisocyanate (TDI), hexamethylene diisocyanate (HDI), isophorone diisocyanate (IPDI), methylene diphenyl diisocyanate (MDI), and their oligomers. Suitable water-soluble reactants include polyols and amines. Suitable polyols are polyols having at least two functional groups, such as ethylene glycol, pentaerythritol, sorbitol, butanediol, hexanediol, pentanediol, and caprolactone diol. Suitable amines include, but are not limited to, diethylenetriamine, ethylenediamine, melamine, hexamethylenediamine, chitosan, gelatin, polyethyleneimine, and guanidine.
[0047] For the formation of a carrier polymer framework from polyacrylates, suitable reactants are selected from acrylates and initiators. Reactants are primarily selected from polyfunctional acrylates and methacrylates, such as allyl methacrylate, dimethacrylate, diacrylate, and butylaminoethyl methacrylate. Suitable water-soluble reactants are initiators, such as peroxy initiators like benzoyl peroxide and ammonium persulfate.
[0048] For the formation of a carrier polymer framework from polyamide and polyester, suitable reactants are selected from acyl dichlorides. The reactants are primarily selected from dichlorides, such as sebacate dichloride, adipate dichloride, and benzenesulfonyl dichloride. Suitable water-soluble reactants are diols and polyols used in the synthesis of polyesters (as described above) and diamines and polyamines used in the synthesis of polyamides (as described above).
[0049] Suitable reactants for using aggregated polymer frameworks as carriers include gelatin and carboxymethyl cellulose, as well as other suitable polymers such as chitosan and ethyl cellulose. Suitable water-soluble reactants include, but are not limited to, glutaraldehyde, carbodiimide, and glyoxal.
[0050] Surfactants prevent droplet coalescence during emulsion preparation, thereby producing a stable emulsion. Suitable surfactants are selected from anionic emulsifiers, cationic emulsifiers, nonionic emulsifiers, and stabilizers. Suitable anionic emulsifiers are sulfates, sulfonates, phosphates, and carboxylates, such as sodium lauryl sulfate, sodium dodecyl sulfate, sodium stearate, and acrylates. Suitable cationic emulsifiers include, but are not limited to, quaternary ammonium salts. Suitable nonionic emulsifiers are all emulsifiers with an HLB value greater than 7. Additionally, stabilizers that act as a steric barrier against oil droplet coalescence and are dissolved in the aqueous phase can be used. Suitable stabilizers include, but are not limited to, carboxymethyl cellulose, polyvinyl alcohol, polysorbate, polyethyleneimine, gum arabic, glyceryl monostearate, and the like.
[0051] Use a dedicated homogenizer and / or a high-speed mechanical stirrer to prepare the emulsion.
[0052] At the phase interface where the reactants in the oil phase and the reactants in the aqueous phase come into contact, a thin polymer layer is formed, thereby capturing the filler material and using it as a carrier framework for subsequent filler deposition into the pores between the polymer chains of the carrier polymer framework and on the surface of the carrier polymer framework.
[0053] Optionally, depending on the choice of polymer, a catalyst may be added during the formation of the polymeric framework of the membrane (during the polymerization step). For example, bismuth neodecanoate or DABCO is used as a catalyst when a support framework is formed from poly(urea-carbamate) in the presence of diisocyanate and polycaprolactone polyol in the oil phase and water-soluble polyol and polyfunctional amine in the aqueous phase. At lower temperatures, diisocyanate reacts only with amines, but with the addition of a catalyst and when the reaction mixture is heated to 80°C, diisocyanate also reacts with polyols to form a support polymeric framework made of poly(urea-carbamate).
[0054] Polymerization was carried out at elevated temperatures for up to 150 minutes, and the reaction was monitored using IR spectroscopy.
[0055] The use of fillers in the preparation of the oil phase (i.e., mixing the filler with a core material having at least one active component) affects the polymerization process. For some active components, particularly some fragrances and ether oils, polymerization is completely hindered or stopped due to the interaction between the reactants and the core material, which reduces the usability of the encapsulation method. By adding fillers to these problematic active components, the results of microencapsulation can be greatly improved. Fillers have good emulsion stabilizing properties and have a positive impact on the encapsulation itself because they effectively dilute the core material and increase the diffusion of reactants to the phase interface of the emulsion droplets (where the carrier polymer framework is formed). In addition to the biodegradability, stability, and brittleness of the microcapsules, fillers also increase the robustness of the encapsulation method described in this invention.
[0056] Figure 1 A cross-section of the microcapsule obtained as described in this invention is shown. The inner diameter R2 represents the thickness of the polymer layer (carrier polymer framework), while the outer diameter R1 represents the thickness of the entire microcapsule membrane (including both the carrier polymer framework and the deposited filler layer). In this example, the membrane thickness is 110 nm to 120 nm.
[0057] Figure 2 The capsule surfaces of a classic polymer membrane microcapsule (right) and a biodegradable microcapsule obtained as described in this invention (left) are shown. The difference in surface appearance is very obvious. The classic microcapsule is very robust and inert, while the biodegradable microcapsule is completely covered by the filler, demonstrating that the filler is present throughout the entire microcapsule surface and further demonstrating the inseparable nature of the composite membrane composed of a carrier polymer framework completely covered by the filler. Figure 2 It is also evident that the filler crystallizes and is therefore largely removed from the oil phase and does not exist in the oil phase in large quantities, nor does it react with the active component in any way.
[0058] Figure 3 The morphology of the microcapsules obtained as described in this invention is shown. The filler covering the entire surface of the microcapsule is clearly visible. Due to the presence of the filler on the surface, the microcapsules also fuse together with the filler, which acts as a binder, to form larger aggregates.
[0059] Figure 4 The pores of the biodegradable microcapsules obtained as described in this invention are shown. It is evident that a large amount of filler is deposited at the locations of the pores on the microcapsule surface.
[0060] By focusing an electron beam onto cracks in the microcapsule membrane, the material is heated to a sufficiently high temperature to melt the crystalline filler. The filler, in its liquid state, is permeable to electrons, allowing the revelation and identification of the carrier polymer framework beneath the crystalline filler layer. This demonstrates that the filler is deposited within the pores of the carrier polymer framework and also on the surface of the microcapsules. Figure 5 The thickness of the filler layer can also be roughly estimated, which is 50 nm to 60 nm in the given example.
[0061] The described steps allow for the synthesis of a range of biodegradable microcapsules with varying properties, depending on the membrane composition and the type and amount of filler used. The type of membrane and the type and amount of filler used depend on the end use of the product. In the case of fragrance encapsulation for fabric softeners and detergents, fragile and highly impermeable microcapsules are advantageous to ensure that the fragrance is released only upon fabric friction. For classic microcapsules, this effect is achieved through thicker and more chemically cross-linked membranes. This invention allows for the synthesis of biodegradable microcapsules with thinner membranes because the membrane's fragility and impermeability are also ensured by the filler, not just the carrier polymer framework. For microcapsules obtained as described in this invention, the membrane also has a lower degree of cross-linking (0% to 20%), and therefore a higher degree of biodegradability. The use of fillers allows for the reduction or even elimination of cross-linking. With 0% cross-linking, the degree of biodegradability is 100% when using biopolymers. Example
[0062] 1. Synthesis of biodegradable microcapsules in aqueous dispersion with a poly(urea-carbamate) polymer carrier framework
[0063] In a reactor, 300g of water, 6g of polyvinyl alcohol (PVA) (Celvol 205), and 3.6g of carboxymethyl cellulose (CMC) (Carbofix 5A) were mixed and heated to 80°C. The mixture was then stirred at 80°C for 1 hour to ensure complete dissolution of the PVA and CMC. The mixture was then cooled to 40°C. Separately, 150g of fragrance (from various manufacturers) was heated to 40°C in a beaker. Then, 20g of wax with a melting point of 44°C, 1.5g of toluene diisocyanate (TDI), 1.5g of polyisocyanate Desmodur N3400, and 1g of CAPA3031 were added to the fragrance and thoroughly mixed. The resulting mixture was then poured into the reactor, and the mixing rate in the reactor was increased. This new mixture was then stirred until emulsion droplets of the desired size of 10μm to 40μm were obtained. After obtaining a suitable emulsion, 10g of a mixture of 5g of cationic surfactant (Lupasol PS) and 5g of diethylenetriamine in a 10% aqueous solution (by weight) was added. The mixture was stirred for 10 minutes, then 10 g of a 50% aqueous solution of xylitol / sorbitol / maltodextrin was added. Immediately following this, BorchiKat 315 catalyst was added, and the mixture was heated to 80°C and maintained at this temperature for 2.5 hours. After this time, the mixture was cooled to room temperature. The final product produced in this manner was an aqueous dispersion of microcapsules containing: 63% (by weight) of an aqueous solution of emulsifier and stabilizer, and 37% (by weight) of microcapsules with a core material and a membrane. 30% (by weight) of the final product was composed of flavoring, which comprised 84% (by weight) of the dry microcapsule weight. The capsule membrane ratio was 16% (by weight) of the dry microcapsule weight.
[0064] 2. Synthesis of biodegradable microcapsules in aqueous dispersion with poly(urea-carbamate) polymer carrier framework at different surfactant ratios
[0065] 230g water, 6g polyvinyl alcohol (PVA) (Celvol 205), and 3.6g carboxymethyl cellulose (CMC) (Carbofix 5A) were mixed in a reactor, heated to 80°C, and mixed at 80°C for 1 hour to ensure complete dissolution of PVA and CMC. The mixture was then cooled to 40°C. Separately, 150g of fragrance (from various manufacturers) was heated to 40°C in a beaker. Then, 20g of paraffin wax with a melting point of 44°C, 2.5g of toluene diisocyanate (TDI), and 2.5g of polyisocyanate Desmodur N3400 were added to the fragrance and mixed thoroughly. The resulting mixture was then poured into the reactor, and the mixing rate in the reactor was increased. This new mixture was then mixed until emulsion droplets of the desired size of 10μm to 40μm were obtained. After obtaining a suitable emulsion, 10g of a mixture of 4g cationic surfactant (Lupasol PS) and 15g of a 10% aqueous solution of diethylenetriamine (by weight) was added. The mixture was stirred for 10 minutes, and then 8 g of a 50% aqueous solution of sorbitol was added. Immediately following this, BorchiKat 315 catalyst was added, and the mixture was heated to 80°C and maintained at this temperature for 2.5 hours. After this time, the mixture was cooled to room temperature. The final product produced in this manner was an aqueous dispersion of microcapsules containing: 56% (by weight) of an aqueous solution of emulsifier and stabilizer, and 44% (by weight) of microcapsules with a core material and a membrane. 34% (by weight) of the final product was composed of fragrance, which comprised 84% (by weight) of the dry microcapsule weight. The capsule membrane ratio was 16% (by weight) of the dry microcapsule weight.
[0066] 3. Synthesis of biodegradable microcapsules in aqueous dispersion with a poly(urea-carbamate) polymer carrier framework for use in detergents
[0067] In a reactor, 309.6 g of water, 6 g of polyvinyl alcohol (PVA) (Celvol 205), and 3.6 g of carboxymethyl cellulose (CMC) (Carbofix 5A) were mixed and heated to 80°C for 1 hour to completely dissolve the PVA and CMC. The mixture was then cooled to 40°C. Separately, 150 g of fragrance (from different manufacturers) was heated to 40°C in a beaker. Then, 30 g of paraffin wax with a melting point of 42°C, 2.5 g of toluene diisocyanate (TDI), and 1.5 g of polyisocyanate Desmodur N3400 were added to the fragrance and mixed thoroughly. The resulting mixture was then poured into the reactor, and the mixing rate in the reactor was increased. This new mixture was then mixed until emulsion droplets of the desired size of 10 μm to 20 μm were obtained. After obtaining a suitable emulsion, 5 g of a 20% aqueous solution of diethylenetriamine (w / w) was added. The mixture was stirred for 10 minutes, and then 1.5 g of dry pentaerythritol was added. Immediately following this, catalyst BorchiKat 315 was added, and the mixture was then heated to 80°C and maintained at this temperature for 1 hour. After 1 hour, 3 g of xylitol / sorbitol / maltodextrin was added, and the mixture was stirred at 80°C for another hour. After this time, the mixture was cooled to room temperature. The final product produced in this manner is an aqueous dispersion of microcapsules containing: 65% (w / w) of an aqueous solution of emulsifier and stabilizer, and 35% (w / w) of microcapsules (including core material and membrane). 30% (w / w) of the final product is composed of flavoring, which constitutes 84% (w / w) of the dry microcapsule weight. The capsule membrane ratio is 16% (w / w) of the dry microcapsule weight.
[0068] 4. Synthesis of biodegradable microcapsules in aqueous dispersion having a gelatin-based polymeric carrier framework and a 21% (w / w) core material content.
[0069] In a reactor, mix 300g of water and 12.4g of gelatin, heat to 50°C, and mix until the gelatin is completely dissolved. Separately, heat 150g of fragrance (from various manufacturers) in a beaker to 50°C, add 10g of paraffin wax with a melting point of 44g, and mix thoroughly. Pour the resulting mixture into the reactor and increase the mixing rate, using a specialized homogenizer if necessary. Mix this new mixture until emulsion droplets of the desired size of 10μm to 20μm are obtained. After obtaining a suitable emulsion, add 8g of carboxymethyl cellulose dissolved in 136g of water. After thorough mixing, add dropwise a 10% (w / w) solution of acetic acid until the pH reaches 4.0. The mixture is then slowly cooled to 10°C for 1 hour and then heated to 20°C at 1°C after 15 minutes. Add dropwise a 50% (w / w) aqueous solution of glutaraldehyde and mix for another 45 minutes. The final product produced in this manner is an aqueous dispersion of microcapsules containing the following: 74% (by weight) water and 26% (by weight) microcapsules (including core material and membrane). 21% (by weight) of the final product is composed of fragrance, which constitutes 88% (by weight) of the dry microcapsule weight. The capsule membrane accounts for 12% (by weight) of the dry microcapsule weight.
[0070] The biodegradable microcapsules obtained through the steps described in this invention retain all the key properties of classic microcapsules. Properties such as the stability of the final product (e.g., fabric softener) and the success of encapsulation of the active ingredient are not significantly altered compared to classic microcapsules, but the microcapsules obtained through the steps described in this invention are biodegradable.
[0071] Analysis of microcapsules
[0072] Steps for determining the stability of microcapsules in fabric softeners:
[0073] The microcapsule dispersion was mixed with a standard fabric softener base (1% by weight) and stored at 40°C to simulate accelerated aging. Fabric softener samples obtained in this manner were examined under a microscope on the day of preparation and then every 7 days for the next 28 days. Based on the microscopic images, samples were assigned a numerical rating indicating the stability of the microcapsules, where a rating of 5 indicates that the capsules retain the core material well, without change, and are not visibly damaged in any way, while a rating of 1 indicates that the microcapsules are completely empty, their core material has completely disappeared, and they are visibly damaged / destroyed.
[0074] The results of this analysis are given in Table 1. Samples 1 to 4 refer to the microcapsules prepared as described in the Examples section of this invention. For classic polymer capsules, the membrane consists only of a carrier framework made of cross-linked poly(urea-urethane).
[0075] Table 1
[0076]
[0077] The results in Table 1 clearly show that the biodegradable microcapsules obtained as described in this invention have a high degree of stability comparable to that of classic microcapsules.
[0078] The most important indicator of encapsulation quality is the final application. To evaluate this parameter, a scraping and smelling technique is used, in which an aqueous dispersion of microcapsules is applied to the target surface and allowed to dry completely. In cases of successful fragrance encapsulation, a strong aroma is released when the surface is rubbed.
[0079] To determine the quality of the microcapsules in terms of fragrance intensity when rubbed against odorless fabric, a fabric softener base with 1% (w / w) of microcapsule dispersion was used. Cotton towels were washed in a washing machine at 40°C, and the prepared sample was used as a fabric softener. After the towels were thoroughly dried, the fragrance intensity was rated on a scale of 1 to 5 when the towels were rubbed, with 5 being the highest rating (most intense fragrance).
[0080] The results are given in Table 2. Samples 1 to 4 refer to the microcapsules prepared as described in the Examples section of this invention. For classic polymer capsules, the membrane consists only of a carrier framework made of cross-linked poly(urea-urethane).
[0081] Table 2
[0082] Classic 5 1 5 2 5 3 3 4 3
[0083] The results in Table 1 clearly show that the biodegradable microcapsules obtained as described in this invention have a high degree of stability comparable to that of classic microcapsules.
[0084] To further confirm that the microcapsules obtained as described in this invention, despite their thin polymer membranes, retain a core material similar to classic microcapsules, we synthesized two types of microcapsules with comparable membrane thicknesses: classic polymer microcapsules with high crosslinking and biodegradable microcapsules as described in this invention. For the classic polymer microcapsules, the membrane consists solely of a polymer network, i.e., a crosslinked poly(urea-urethane) network, with a membrane thickness of 100 nm to 150 nm, while the microcapsules obtained as described in Example 1 of this invention have a membrane wall thickness of 110 nm to 120 nm. Gravimetric analysis at 50°C showed that the biodegradable microcapsules obtained as described in this invention exhibited a much slower sample mass degradation and reached equilibrium more quickly compared to classic microcapsules without filler material. This indicates that the membranes obtained as described in this invention have fewer pores and therefore lower fragrance permeability.
[0085] These results were further confirmed by stability tests in fabric softeners. Classic microcapsules without filler material performed much worse in retaining the core material and were completely vacant after 7 days. Figure 6 Furthermore, the biodegradable microcapsules obtained as described in this invention still contain most of the core material even after 28 days.
[0086] Rapid breath measurement method for biodegradability testing
[0087] Comparable respiration rate tests were performed in reagent bottles according to standard method 5210 (BIOCHEMICAL OXYGEN DEMAND, BOD) (2017). These tests were conducted on a mineral substrate containing 250 mL of deionized water supplemented with the following nutrients:
[0088] 1. BPK1 (phosphate buffer)
[0089] KH2PO4 8.5mg / l
[0090] K2HPO4 21.75mg / l
[0091] Na₂HPO₄x₇H₂O 33.4 mg / L
[0092] NH4Cl 1.7 mg / L
[0093] 2. BPK2 (Magnesium Sulfate)
[0094] MgSO4x7H2O 22.5mg / l
[0095] 3. BPK3 (calcium chloride)
[0096] CaCl2 27.5 mg / L
[0097] 4. BPK4 (ferric chloride)
[0098] FeCl3x6H2O 0.25mg / l
[0099] In the classic respiratory quantification test, a mixture of glucose and glutamate (GGA) (300 mg / L) was used as a positive control sample. A mixture of bacterial cultures from the laboratory was used as an inoculum.
[0100] Description of the test method
[0101] First, the microcapsules obtained as described in this invention were mechanically damaged using a planetary ball mill. Then, the fragrance was evaporated, and the resulting dried sample was dispersed in clean water. The amount of microcapsule dispersion was calculated such that the final dispersion of added membrane material totaled 100 mg of membrane material.
[0102] - The microcapsule dispersion obtained as described in Example 1 of this invention: 0.12 mL
[0103] -Inoculum: 10mL
[0104] - Distilled water: 238.88 mL
[0105] -BPK: 0.25μL.
[0106] Results of rapid breath measurement biodegradability test ( Figure 7 It is evident that microcapsules with biodegradable filler materials (composite membranes) obtained as described in this invention degrade much faster than classic polymer microcapsules. The latter exhibits a higher biodegradability than the positive control sample (GGA) containing glucose.
[0107] OECD 301 Closed Bottle Biodegradability Test
[0108] To determine the biodegradability of the microcapsule sample obtained as described in Embodiment 1 of this invention, a biodegradability test was performed according to OECD 301F (determination of inherent biodegradability by measuring oxygen consumption in a closed breathalyzer). This test is listed by the European Chemicals Agency (ECHA) as a suitable method for testing the biodegradability of microplastics.
[0109] a) Description of the testing method
[0110] Microcapsule sample 1 was prepared by filtering and rinsing the aqueous dispersion of the microcapsules with water to remove water-soluble components (emulsifiers, unreacted reactants). The sample obtained in this manner was then dried at 80°C to remove the fragrance from the microcapsule core. The dry solid residue of the sample consisted only of the microcapsule membrane and was used as the sample to be used in the biodegradability test.
[0111] For this test, we used activated sludge from a municipal wastewater treatment plant. The sludge was collected one day prior to the biodegradability test, washed with tap water at least five times, and its concentration (mg MLVSS / L) was determined by filtering 20 mL of activated sludge suspension through black filter paper. The sludge was then placed in a climate chamber (22±2℃) and aerated until use.
[0112] The biodegradability assessment test was one of the optional tests used to determine inherent biodegradability. It was based on the measurement of oxygen consumption in a closed breather, where biodegradation was indirectly measured by oxygen consumption over 40 days at a constant temperature of 20 ± 1 °C. The activated sludge concentration in the test was 30 mg / L. No pH adjustment was required before the test, as the pH of the test mixture was 7.8 ± 0.0 (optimal range 6 to 8). Simultaneously, a reference material (sodium acetate) was used to determine the typical conditions for microbial activity and biodegradation throughout the test. Non-biodegradation was also determined in a system without activated sludge added to the mixture and chemically sterilized by adding HgCl2. The sample concentration in the test was 0.18 vol% (COD = 100 mg / L). Non-biodegradation was also measured using the same sample concentration. All tests were performed in parallel. A test was also conducted with the same sample concentration and the addition of allyl thiourea-ATU (4 mL / L) as a nitrification inhibitor. Therefore, the measured oxygen consumption was proven to be due to (bio)degradation of the sample rather than nitrification.
[0113] b) Test Results
[0114] The average chemical oxygen demand (COD) was determined. The pH of the microcapsule samples was 7.5 ± 0.1.
[0115]
[0116] Simultaneously, we measured oxygen consumption in blank samples, tests with a reference substance (sodium acetate), samples, and non-biological samples. We also examined oxygen consumption in the following samples: blank samples and samples with added ATU to ensure that nitrification (oxidation of ammonium, which is not a (bio)degradation of the sample) and the resulting oxygen consumption did not occur. The initial pH of the mixture was in the range of 7.7 ± 0.1, therefore, according to standard ISO procedures, pH adjustment was not required, and the pH of the samples had no effect on biodegradation.
[0117] The results show ( Figure 8The reference compound degraded well. Degradation was greater than 60% after only 5 days. This confirms the activity of the microorganisms, the suitability of the test, and the validity of the results. The sample also degraded well in the test. Greater than 80% (85±3%) degradation was achieved during the 40-day test. This degradation level was reached on day 17 of the test, followed by a 3-day lag period. Rapid degradation of the sample was also confirmed in the test using samples with added ATU (added to prevent nitrification and the resulting oxygen consumption), as complete degradation (99±2%) was achieved in this case. Since the degradation in the sample with ATU was comparable to or even higher than that in the sample without ATU, it can be concluded that the difference between the two curves is due to experimental error or more precisely, due to the test principle, and that no nitrification occurred. This means that the actual biodegradation of the sample reached as high as 85%, with very little non-biodegradation (6±0%). It can be concluded that the degradation level obtained is primarily a result of microbial activity (biodegradation).
Claims
1. A method for synthesizing an aqueous dispersion of biodegradable microcapsules from an emulsion, wherein the microcapsules comprise: A core material comprising at least one water-immiscible liquid active component, and a membrane encapsulating the liquid core material, wherein the membrane comprises a composite material containing a carrier polymer framework and at least one filler embedded in the pores of the polymer framework and deposited on the surface of the carrier polymer framework, wherein the carrier polymer framework comprises at least one polymer selected from polyurea, polyurethane, polyacrylate, polyamide, polyester, or gelatin, and the filler is a lipophilic biodegradable organic compound that is solid at room temperature and has a melting temperature above 40°C, the method comprising the following steps: a) Preparing an oil phase, wherein the liquid core material to be encapsulated is mixed with the filler and a first reactant at a temperature of 40°C to 70°C, wherein the first reactant is a chemical substance that is mixed with the core material and forms the carrier polymer framework comprising at least one polymer during polymerization; b) Prepare an aqueous phase at a temperature above 40°C, said aqueous phase comprising an aqueous solution of a biodegradable surfactant; c) A stable emulsion is prepared at a temperature of 40°C to 70°C, wherein the oil phase is emulsified in the aqueous phase to form emulsion droplets of the same size as the microcapsules formed; d) The carrier polymer framework forming the membrane from at least one polymer, wherein the formation of the carrier polymer framework is triggered at the phase boundary around the dispersed droplets by adding a second reactant, which is a water-soluble reactant, to the stabilizing emulsion, and thus triggers the formation of an aqueous dispersion having microcapsules of a carrier polymer framework membrane surrounding the liquid core material; e) The aqueous dispersion of the microcapsules is controlled-cooled to a temperature of 10°C to 25°C, whereby the filler crystallizes and embeds itself in the pores and is deposited on the surface of the carrier polymer framework membrane, thereby forming a final aqueous dispersion of biodegradable microcapsules with a mass fraction of 25% to 50%, the biodegradable microcapsules having a membrane surrounding the core material comprising the carrier polymer framework and the filler, wherein the diameter of the microcapsules is in the range of 1 μm to 50 μm, and the thickness of the membrane is in the range of 20 nm to 200 nm.
2. The synthesis method according to claim 1, wherein the method optionally includes step f), wherein a stabilizer is added to the aqueous dispersion of the microcapsules to prevent separation of the microcapsules from the aqueous phase in the aqueous dispersion, and / or residual reactants are added to complete the polymerization or eliminate excess reactants, and / or a pH adjuster is added, wherein step f) after step d) means that these additives are added to the aqueous dispersion before controlled cooling, or step f) after step e).
3. The synthesis method according to any one of claims 1 and 2, wherein the liquid active component in the core material is present as a pure compound or dissolved in an organic solvent, wherein the organic solvent is immiscible with water and is chemically inert to the active component and the reactants used to form the composite material.
4. The synthesis method according to any one of claims 1 and 2, wherein the liquid active component is selected from fragrances; pigments; pesticides; phase change materials; ether oils; other oils; and photochromic materials, wherein the ether oils include eucalyptus oil, lavender oil, rose oil, common valerian oil, basil oil, juniper berry oil, lemongrass oil, and lemongrass oil, and the other oils include palm oil, coconut oil, castor oil, sunflower oil, olive oil, and mineral oil.
5. The synthesis method according to any one of claims 1 and 2, wherein, in order to form the carrier polymer framework from polyurea and polyurethane, the reactants in step a) are selected from aromatic isocyanates or aliphatic isocyanates having at least two functional groups, and the water-soluble reactants in step d) are selected from amines or polyols having at least two functional groups.
6. The synthesis method according to any one of claims 1 and 2, wherein, in order to form the carrier polymer framework from polyacrylate, the reactants in step a) are selected from polyfunctional acrylates and methacrylates, and the water-soluble reactants in step d) are peroxide initiators.
7. The synthesis method according to claim 6, wherein the peroxide initiator comprises benzoyl peroxide and ammonium persulfate.
8. The synthesis method according to any one of claims 1 and 2, wherein, in order to form the carrier polymer framework from polyamide or polyester, the reactants in step a) are selected from acidic dichlorides, and the water-soluble reactants in step d) are selected from diols or polyols used for synthesizing polyesters and diamines and polyamines used for synthesizing polyamides.
9. The synthesis method according to any one of claims 1 and 2, wherein, in order to form the carrier polymer framework by aggregation, the reactants in step a) are selected from gelatin, chitosan or ethyl cellulose, and the water-soluble reactants in step d) are selected from glutaraldehyde, carbodiimide or glyoxal.
10. The synthesis method according to any one of claims 1 to 2, wherein the surfactant is selected from anionic emulsifiers, cationic emulsifiers, nonionic emulsifiers, and stabilizers, wherein the anionic emulsifier is selected from sulfates, sulfonates, phosphates, and carboxylates, the cationic emulsifier is a quaternary ammonium salt, the nonionic emulsifier is any emulsifier with an HLB value greater than 7, and the stabilizer is selected from carboxymethyl cellulose, polyvinyl alcohol, polysorbate, polyethyleneimine, gum arabic, and glyceryl monostearate.
11. The synthesis method according to any one of claims 1 to 2, wherein optionally, a catalyst is added during polymerization when forming the support polymer framework.
12. An aqueous dispersion of biodegradable microcapsules produced by the method according to any one of claims 1 to 11, wherein the microcapsules comprise: A core material comprising at least one water-immiscible liquid active component, and a membrane encapsulating the liquid core material, wherein the membrane comprises a composite material containing a carrier polymer framework and at least one filler embedded in the pores of the polymer framework and deposited on the surface of the carrier polymer framework, wherein the carrier polymer framework comprises at least one polymer selected from polyurea, polyurethane, polyacrylate, polyamide, polyester, or gelatin, and the filler is a lipophilic biodegradable organic compound that is solid at room temperature and has a melting temperature above 40°C, wherein the diameter of the microcapsules is in the range of 1 μm to 50 μm, and the thickness of the membrane is in the range of 20 nm to 200 nm.
13. The aqueous dispersion of the biodegradable microcapsules according to claim 12, wherein the filler comprises 50% to 90% by weight relative to the weight of the polymer.
14. Use of the aqueous dispersion of the biodegradable microcapsules according to any one of claims 12 and 13 in fabric softeners, detergents, pesticides, coatings and cosmetics.
Citation Information
Patent Citations
Microencapsulated insecticide formulations
EP2403333A1
Encapsulation of perfumes
US20150044262A1
Microencapsulation process
US4956129A
Microcapsules and microencapsulation process
US5160529A
Microcapsules, method of making and their use
CN1139386A